A Convergent Total Synthesis of the Biologically Active Benzofurans Ailanthoidol, Egonol and Homoegonol from Biomass-Derived Eugenol - Espinoza-Hicks, José C.; Zaragoza-Galán, Gerardo; Chávez-Flores, David; Ramos-Sánchez, Víctor H.; Tamariz, Joaquín; Camacho-Dávila, Alejandro A. (Synthesis, 2018)
An efficient, general synthetic protocol for the synthesis of the biologically active benzofurans ailanthoidol, egonol and homoegonol was developed. The key starting material, eugenol, is a naturally occurring and abundant precursor. The protocol, involving sequential acylation and intramolecular Wittig reaction, provides a convenient method for building the benzofuran moiety in good yield.
Keywords: benzofurans; ailanthoidol; egonol; homoegonol; sustainable synthesis; total synthesis; natural products